The Effect of Payment Schemes on Inventory Decisions: The Role of Mental Accounting - Chen, Li; Kök, A. Gürhan; Tong, Jordan D. (Management Science, 2013)
Does the payment scheme have an effect on inventory decisions in the newsvendor problem? Keeping the net profit structure constant, we examine three payment schemes that can be interpreted as the newsvendor's order being financed by the newsvendor herself (scheme O), by the supplier through delayed order payment (scheme S), and by the customer through advanced revenue (scheme C). In a laboratory study, we find that inventory quantities exhibit a consistent decreasing pattern in the order of schemes O, S, and C, with the order quantities of scheme S being close to the expected-profit-maximizing solution. These observations are inconsistent with the expected-profit-maximizing model, contradict what a regular or hyperbolic time-discounting model would predict, and cannot be explained by the loss aversion model. Instead, they are consistent with a model that underweights the order-time payments, which can be explained by the “prospective accounting” theory in the mental accounting literature. A second study shows that the results hold even if all physical payments are conducted at the same time, suggesting that the framing of the payment scheme is sufficient to induce the prospective accounting behavior. We further validate the robustness of our model under different profit conditions. Our findings contribute to the understanding of the psychological processes involved in newsvendor decisions and have implications for supply chain financing and contract design. This paper was accepted by Christian Terwiesch, operations management.